OsLB2.2 negatively regulates rice disease resistance at seedling stage in rice - Ma, Tianze; Wang, Mengge; Xie, Shupeng; Li, Chengxin; Wang, Jingguo; Liu, Hualong; Yang, Luomiao; Men, Longnan; Sun, Zhonghua; Zong, Tianpeng; Zou, Detang; Zheng, Hongliang; et al. (Frontiers in Plant Science, 2025)
BackgroundRice blast disease, caused by the fungal pathogen Magnaporthe oryzae, stands as the most destructive diseaset of rice, negatively impacting yield and quality. Identification of blast resistance genes is crucial for breeding disease resistant varieties. In this study, we conducted a genome-wide association analysis on rice blast with 295 Japonica rice varieties and the rice blast dominant physiological race ZD5 from Heilongjiang.ResultsA total of 11 Quantitative Trait Loci (QTLs) encompassing 233 genes were mapped. Notably, 40 genes showed significant phenotypic variations among different haplotypes. By combining GWAS and RNA sequencing analysis, we identified five candidate genes related to rice seedling resistance to rice blast. Through the assessment of relative gene expression levels in 10 susceptible and 10 resistant varieties, OsLB2.2 (LOC_Os02g57470) emerged as a key gene displaying significant expression differences in resistant varieties under uninoculated and inoculated conditions. To elucidate gene functionality, we generated oslb2.2 knockout mutants. The results showed that oslb2.2 knockout mutants were significantly enhanced rice blast resistance compared to the wild type. Furthermore, we identified the dominant haplotype of OsLB2.2 and developed Kompetitive Allele - Specific PCR (KASP) molecular markers for molecular improvement of rice blast resistance.ConclusionThe phenotypic validation indicated that OsLB2.2 negatively regulated the rice blast resistance at the seedling stage. Moreover, KASP molecular markers were developed, providing a theoretical basis for the potential application of OsLB2.2 in molecular breeding strategies.